The Suitable Model of Branchless Banking Implementation in Indonesia - Shabirah, Iffah; Aldianto, Leo (Journal of Business and Management, 2014)
Branchless banking as the new distribution channel in banking industry is becoming a new solution to offer financial service to untapped society. Branchless banking will help Indonesia to decrease its number of unbanked people. This Final project is to find out the right model of branchless banking that can be implemented in Indonesia, regarding the society respond and hope towards banking the reliable technology, collaboration of parties that involve, and how to avoid branchless banking risks. The respond and hope society towards banking measured by spreading the questionnaires to 112 middle class society in Depok. The questionnaires results were calculated by frequency analysis method. The reliable technology, collaboration of parties, and the way to avoid risks were find out by interviewing three people from different parties, which are Telkomsel from Telco Company, Bank BJB, and PT Cyberport as the company between bank and Telco. The result of this research is, branchless banking in Indonesia can be implemented by collaboration of Telco Company, Bank, and private sector. The reliable technology to implement branchless banking is using USSD connectivity and EDC machine that has been modified to be branchless banking technology. The risks in branchless banking can be avoided by risks mitigation from technology and regulation. The respondents’ perception towards banking is, bank is secure but bank do not have flexible opening hour. The expectation of respondents is bank become more secure, flexible, and have easier way and requirement to open bank account. To create a suitable model of branchless banking in Indonesia, those three parties have to conduct another similar research in the different area, to know the demand of the society. After those parties knowing about society needs and demand, they should do the three approaches to meet the demand. Those approaches are Price, feature, and process approach.Keyword: Branchless banking, Collaboration, reliable technology, perception, expectation